The Effectiveness of Voicemaker Learning Media in Improving the Arabic Listening Skills of Seventh-Grade Students at MTs Alif Laam Miim Surabaya - Naashirul Haq; Hizbullah Huda; Ahmad Shofiyyul Mubarok (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2026)
This study investigated the effectiveness of AI-based Voicemaker in improving Arabic listening skills (maharah al-istima') among seventh-grade students at MTs Alif Laam Miim Surabaya. A quantitative approach with a quasi-experimental design was employed, involving all 47 students who were assigned to an experimental group using Voicemaker and a control group receiving conventional instruction. Data were collected through listening achievement tests and questionnaires and analyzed using descriptive statistics, the Shapiro–Wilk test, Levene's test, the Independent Samples t-test, and the Mann–Whitney U test with JASP software. The findings revealed a significant difference between the two groups (p < 0.001), with the experimental group obtaining a higher mean score (54.76) than the control group (44.71). The Mann–Whitney U test confirmed a significant difference with a large effect size (0.681), indicating that Voicemaker substantially improved students' Arabic listening skills. Its AI-based Text-to-Speech technology provided clear, natural, and repeatable audio, enabling students to improve pronunciation, intonation, and listening comprehension. This study contributes empirical evidence supporting the integration of AI-assisted Text-to-Speech technology into Arabic listening instruction, offering educators an effective, interactive, and learner-centered instructional approach.